Answer:
B. ) x² + 4x + 3
Step-by-step explanation:
(f-g)(x) = f(x) - g(x) =
(2x²-5) - (x²-4x-8) =
2x² - x² + 4x + 8 - 5 =
x² + 4x + 3
Answer:
3.6cm
Step-by-step explanation:
Given data
We are given that the dimension of the photo is
Height= 15cm
Width= 9cm
That is
15cm height will make 9cm width
hence 6cm height will make x widht
cross multiply
9*6= 15*x
54= 15x
x= 54/15
x= 3.6cm
Hence the width will be 3.6cm
Answer: 9.5 cups of water
Step-by-step explanation:
5 1/2 + 4
5 1/2= 11/2
11/2+4=9.5
17x+3y+5 if you just want to add common factors